Analisis Wacana Kritis Konten Youtube Caknun.com pada Playlist Jurnal Medsos dan Rahmatan Lil’alamin - Romeli; Luthfi Ulfa Ni’amah (El Madani : Jurnal Dakwah dan Komunikasi Islam, 2023)
This study seeks to explain Cak Nun's da'wah messages related to social media. The approach used is the theory of critical discourse analysis modeled by Teun A. van Dijk which describes three levels, namely text content, social cognition, and social context. The results of the study explain that Cak Nun invites all people to be wise in using social media and to be able to use social media properly to foster grace for all mankind. This starts with self-applied behavior or attitude of responsibility and awareness in using it so that it can spread benefits to others. Social media can greatly influence humans to obtain thoughts about religion through da'wah content on social media. With this, the use of social media for good can make it one of the tools to compete in terms of goodness to create a harmonious society and one form of creating world peace.